DEVELOPING AND MEASURING SOFT SKILLS AFTER ONLINE TRAININGS - Ivona Litsova (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
Working remotely has become a common approach for many companies in the past year. This raises several questions including the work-life balance and worker’s effectiveness in the home-office environment. Here also comes the question of the training of employees and how to develop them in the new working set-up. Online programs become more and more popular among the employers. They can be in the form of webinars, virtual classrooms, conferences, etc. A focus of this article is to outline the ways to measure soft skills after online trainings. I did a literature review which covers books and journals on soft skills measurement topic with the purpose to clarify the methodology for evaluation of the results after online courses. The article provides additional findings from the conducted survey among the regular employees in a technical company from the IT sector in Eastern Europe. The outcomes from it confirmed that reactions are what organizations usually measure and it is done by using feedback forms during or after the course which helps to improve the future sessions. Learning objectives should be defined in advance and can be measured during the training by carefully observing the participation of the trainees. Results could be measured on a later stage after careful consideration of the productivity of the employee and analysis of his/ her feedback, behavior and changes in the working process after the course. Kirkpatrick’s model will be the starting point of the discussion in the context of the following steps for evaluation – reaction, learning, behavior and results.
Keywords: soft skills, training and development, online courses, training evaluation